2017
DOI: 10.1038/srep39760
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cell generation from a man carrying a complex chromosomal rearrangement as a genetic model for infertility studies

Abstract: Despite progress in human reproductive biology, the cause of male infertility often remains unknown, due to the lack of appropriate and convenient in vitro models of meiosis. Induced pluripotent stem cells (iPSCs) derived from the cells of infertile patients could provide a gold standard model for generating primordial germ cells and studying their development and the process of spermatogenesis. We report the characterization of a complex chromosomal rearrangement (CCR) in an azoospermic patient, and the succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…However, a CRISPR/ Cas9 genome editing strategy has been successful in modelling putatively deleterious variants in mouse orthologues of human fertility genes [85]. Alternatively, generating primordial germ cells using induced pluripotent stem cells from infertile patients is likely to provide valuable in vitro genetic models to improve our understanding of meiotic mechanisms causing infertility in humans [87].…”
Section: (B) Meiosis Recombination and Infertilitymentioning
confidence: 99%
“…However, a CRISPR/ Cas9 genome editing strategy has been successful in modelling putatively deleterious variants in mouse orthologues of human fertility genes [85]. Alternatively, generating primordial germ cells using induced pluripotent stem cells from infertile patients is likely to provide valuable in vitro genetic models to improve our understanding of meiotic mechanisms causing infertility in humans [87].…”
Section: (B) Meiosis Recombination and Infertilitymentioning
confidence: 99%
“…For these reasons, how mice iPSC line differentiates into germ cells of males was assessed both in vivo and in vitro. Induced pluripotent stem cells (iPSCs) possessed ESC-like morphology and markers of pluripotency, in addition to possessing the capability of producing three germ layers and finally male germ cells (Cai et al, 2013;Mouka et al, 2017;Pourmoghadam et al, 2018). The use of MSCs for the reasons already mentioned is extensive and has also been studied for male infertility treatment (Fazeli et al, 2018).…”
Section: Cell-based Therapy Approaches In Treating Male Infertilitymentioning
confidence: 99%
“…Human stem cell and especially reprogrammed stem cell disease modeling studies are still establishing such parameters, but it is noteworthy that numerous studies beyond the current one build on the analysis of this LRRK2 G2019S mutation originally described by one of the authors and focusing on an exemplary gene identified case (Nguyen et al, ); in many ways, this case and these iPSC lines are still exemplary of this gene‐identified PD phenotype and still worthy of study in comparison with a sibling control and gene corrected lines, in addition to idiopathic PD cases (the AHNP studies, as originally described in Wang et al, ). Furthermore, numerous iPSC studies with extreme clinical relevance have relied on the same or even smaller sample sizes, be it either chromosomal aberrations including duplications as in certain psychiatric disorders as from a single 5q11.2‐q13.1 duplication syndrome patient (Arioka, Kushima, Mori, & Ozaki, ) or chromosomal rearrangements involved in reproduction (Mouka et al, ), or analysis of iPSC‐derived retinal cells from one patient with macular degeneration (Mandai et al, ), these studies do provide significant and important cell and molecular information toward establishing the molecular signatures of different human stem cell populations in spite of inherent cross‐patient omics variability that nonetheless exhibit much less disparity between biological replicates from the same case. The analysis of exosomes from the current cases adheres to guidelines established by one of the authors for satisfying minimal information requirements for studies of extracellular vesicles and their distinctive and patient−/disease‐specific RNA, DNA, and protein cargoes (Thery et al, ).…”
Section: Discussionmentioning
confidence: 99%